La reconstrucció lingüística vista per un romanista . Problemes de mètode. Esguard retrospectiu. Perspectives - Blasco Ferrer, Eduard (Caplletra. Revista Internacional de Filologia, 2015)
This paper presents a critical view of the primary contribution of the Neogrammarians, structuralist and generative linguistics, and language typology studies to historical linguistics. The author suggests that historical analyses would benefit from incorporating insights from sociolinguistics and dialectology.